Study on the contrast of the MHC–peptide interaction of B2/B21 haplotype and MHC‐related virus resistance in chickens - Yuan‐chang Jin (Wiley, 2021)
Abstract Introduction Three‐dimensional (3D) structures of MHC class I exert some influence by the MHC–peptide interaction over host resistance to the virus. The thesis aims at studying the connection between MHC–peptide interaction of B2/B21 haplotype and MHC‐related resistance to the virus. Methods The structure of chicken MHC class I BF2*0201 from B2 haplotype was studied and contrasted with that of BF2*2101 from B21 haplotype by using DNAMAN and PyMol software. Results The amino acid difference resulted in the difference in size and changeability of the binding groove of the two, resulting in different choices on the binding polypeptide. 3bew's (the crystal structure of BF2*2101 bound to peptide RV10) small side chain His111 replaces the short side chain Tyr111 of 4cvx (the crystal structure of BF2*0201 bound to peptide YL9), and the very small amino acid of Ser69 and Ser97 make the middle of the 3bew's binding groove become apparently broad and bound restrictive of amino acid smaller. Moreover, due to the specific amino acids—Arg9, Asp24, and Asp73 of 4cvx and Arg9, Asp24, and His111 of 3bew, the effect of the polypeptide and the binding groove differ between the two, and 3bew tends to bind polypeptides with negatively charged amino acids, but the large space in the middle can also accommodate other amino acids. Contrasted with the binding groove characteristic of 4cvx, it can be said that the selectivity of 3bew is higher than that of 4cvx in the amino acid type of the binding polypeptide, so the B21 haplotype has more host resistance to the virus than that of the B2 haplotype in chicken. Conclusion There are usually various kinds of peptides presented by the BF2*2101 molecules of B21 haplotypes, resulting in resistance to pathogenic microorganisms, such as Rous sarcoma virus and/or Marek's disease virus. These findings may have an important theoretical foundation for screening of virus antigen, vaccine design, and genetic resistance breeding.